Direct versus Indirect Colonial Rule in India: Long-Term Consequences - Iyer, Lakshmi (The Review of Economics and Statistics, 2010)
This paper compares economic outcomes across areas in India that were under direct British colonial rule with areas that were under indirect colonial rule. Controlling for selective annexation using a specific policy rule, I find that areas that experienced direct rule have significantly lower levels of access to schools, health centers, and roads in the postcolonial period. I find evidence that the quality of governance in the colonial period has a significant and persistent effect on postcolonial outcomes.